Exploring the relationship between plural values of nature, human well‐being, and conservation and development intervention: Why it matters and how to do it? - Carmenta, Rachel; Zaehringer, J. G.; Balvanera, P.; Betley, E.; Dawson, N.M.; Estrada-Carmona, Natalia; Forster, J.; Hoelle, J.; Lliso, B.; Llopis, J. C.; Menon, A.; Moeliono, M.; et al. (Wiley, 2023)
Abstract Globally, land and seascapes across the bioculturally diverse tropics are in transition. Impacted by the demands of distant consumers, the processes of global environmental change and numerous interventions seeking climate, conservation and development goals, these transitions have the potential to impact the relationships and plurality of values held between people and place. This paper is a Synthesis of seven empirical studies within the Special Feature (SF): ‘What is lost in transition? Capturing the impacts of conservation and development interventions on relational values and human wellbeing in the tropics’. Through two Open Forum workshops, and critical review, contributing authors explored emergent properties across the papers of the SF. Six core themes were identified and are subsumed within broad categories of: (i) the problem of reconciling scale and complexity, (ii) key challenges to be overcome for more plural understanding of social dimensions of landscape change and (iii) ways forward: the potential of an environmental justice framework, and a practical overview of methods available to do so. The Synthesis interprets disparate fields and complex academic work on relational values, human well‐being and de‐colonial approaches in impact appraisal. It offers a practical and actionable catalogue of methods for plural valuation in the field, and reflects on their combinations, strengths and weaknesses. The research contribution is policy relevant because it builds the case for why a more plural approach in intervention design and evaluation is essential for achieving more just and sustainable futures, and highlights some of the key actions points deemed necessary to achieve such a transition to conventional practice. Read the free Plain Language Summary for this article on the Journal blog.